A Preliminary Investigation of The Alkaloid of Phoebe Lanceolata - Dayar Arbain; Melvyn V. Sargent (ASEAN Journal on Science and Technology for Development, 1987)
A Preliminary Investigation of The Alkaloid of Phoebe Lanceolata